2005
DOI: 10.1079/nrr2005109
|View full text |Cite
|
Sign up to set email alerts
|

Determining the relationship between dietary carbohydrate intake and insulin resistance

Abstract: Insulin resistance underlies type 2 diabetes, CVD and the metabolic syndrome, driven by changes in diet, lifestyle, energy over-consumption and obesity. Nutritional recommendations for insulin resistance remain an area of controversy, particularly the quantity and types of dietary carbohydrate. The present review gives an overview of insulin resistance, its relationship to impaired insulin secretion and the metabolic syndrome, research methodologies used to measure insulin action and the epidemiological and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 167 publications
1
18
0
3
Order By: Relevance
“…Some small scale and short-term intervention studies designed to assess the effects of high carbohydrate (50 to 85%E), low fat (<25E%) vs low carbohydrate (8 to 40%E), high fat (>35%) intakes on measures of glucose tolerance or insulin sensitivity suggest that high carbohydrate intakes may improve insulin sensitivity and/or glucose tolerance both in non-diabetic and diabetic subjects (McClenaghan, 2005), although the available data are not consistent (IoM, 2005).…”
Section: Glucose Tolerance and Insulin Sensitivitymentioning
confidence: 99%
“…Some small scale and short-term intervention studies designed to assess the effects of high carbohydrate (50 to 85%E), low fat (<25E%) vs low carbohydrate (8 to 40%E), high fat (>35%) intakes on measures of glucose tolerance or insulin sensitivity suggest that high carbohydrate intakes may improve insulin sensitivity and/or glucose tolerance both in non-diabetic and diabetic subjects (McClenaghan, 2005), although the available data are not consistent (IoM, 2005).…”
Section: Glucose Tolerance and Insulin Sensitivitymentioning
confidence: 99%
“…First, no control for important confounding factors known to significantly affect insulin sensitivity, such as physical activity levels (16), body composition (17), and food intake (18), was provided in these studies, which might have influenced these results. Second, fasting insulin levels and HOMA IR are static estimates thought to primarily reflect hepatic insulin sensitivity as they rely on basal steady-state measures of glucose and insulin (5,19).…”
Section: Introductionmentioning
confidence: 99%
“…These results therefore cannot be extrapolated to humans taking more palatable levels of sucrose or fructose. Studies in human subjects show variable effects with alterations of dietary sucrose intake when using simple measures of insulin sensitivity (16). One small study in seven subjects without diabetes demonstrated that a high-glycemic index diet (25% sucrose) was associated with detrimental effects on insulin sensitivity compared with a low-glycemic index diet (1.2% sucrose) over 4-week dietary periods (17).…”
mentioning
confidence: 99%